Potassium Iodide Potentiates Broad-Spectrum Antimicrobial Photodynamic Inactivation Using Photofrin - Huang, Liyi (ACS Infect Dis, 2017)
It is known that noncationic porphyrins such as Photofrin (PF) are effective in mediating antimicrobial photodynamic inactivation (aPDI) of Gram-positive bacteria or fungi. However, the aPDI activity of PF against Gram-negative bacteria is accepted to be extremely low. Here we report that the nontoxic inorganic salt potassium iodide (KI) at a concentration of 100 mM when added to microbial cells (10(8)/mL) + PF (10 μM hematoporphyrin equivalent) + 415 nm light (10 J/cm(2)) can eradicate (>6 log killing) five different Gram-negative species (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Proteus mirabilis, and Acinetobacter baumannii), whereas no killing was obtained without KI. The mechanism of action appears to be the generation of microbicidal molecular iodine (I(2)/I(3)(−)) as shown by comparable bacterial killing when cells were added to the mixture after completion of illumination and light-dependent generation of iodine as detected by the formation of the starch complex. Gram-positive methicillin-resistant Staphylococcus aureus is much more sensitive to aPDI (200–500 nM PF), and in this case potentiation by KI may be mediated mainly by short-lived iodine reactive species. The fungal yeast Candida albicans displayed intermediate sensitivity to PF-aPDI, and killing was also potentiated by KI. The reaction mechanism occurs via singlet oxygen ((1)O(2)). KI quenched (1)O(2) luminescence (1270 nm) at a rate constant of 9.2 × 10(5) M(−1) s(−1). Oxygen consumption was increased when PF was illuminated in the presence of KI. Hydrogen peroxide but not superoxide was generated from illuminated PF in the presence of KI. Sodium azide completely inhibited the killing of E. coli with PF/blue light + KI.